2016
DOI: 10.1016/j.gdata.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of Solanum lycopersicum and Solanum habrochaites under drought conditions

Abstract: Drought is one of the limiting environmental factors that affect crop production worldwide. Understanding the molecular mechanism of drought stress is the key to developing drought tolerant crop. In this experiment we performed expression profiling of tomato plants under water deficit conditions using microarray technology. The data set we generated (available in the NCBI/GEO database under GSE22304) has been analyzed to identify genes that are involved in the regulation of tomato's responses to drought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…The L12 experiment correspond to drought stress considering samples of leaves from four-week-old S. lycopersicum and S. habrochaites , previously non-irrigated for 14 days. Finally, the L13 experiment corresponded to a heat stress assay considering samples of leaves from four-week-old S. lycopersicum and S. habrochaites treated at 40 °C [47]. The profiles are relative to the control without stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The L12 experiment correspond to drought stress considering samples of leaves from four-week-old S. lycopersicum and S. habrochaites , previously non-irrigated for 14 days. Finally, the L13 experiment corresponded to a heat stress assay considering samples of leaves from four-week-old S. lycopersicum and S. habrochaites treated at 40 °C [47]. The profiles are relative to the control without stress.…”
Section: Methodsmentioning
confidence: 99%
“…Heat stress: S. lycopersicum versus S. habrochaites (GEO accession GSE22304). RNA extraction from leaves of four-week-old plants treated at 40 °C [47]. All values are detailed in Table S7.…”
Section: Figurementioning
confidence: 99%
“…In addition to genetic studies conducted at the DNA level, efforts have also been made in candidate gene discovery through RNA deep sequencing ( Chang et al , 2016 ; Garg et al , 2016 ; Shankar et al , 2016 ) and microarray analysis ( Mishra et al , 2016 ). For example, whole-genome transcriptome-profiling studies have identified a large number of transcripts encoding members of various gene families reported to play an important role in abiotic stress tolerance, including AP2/EREBP , bLHL , MYB , and auxin-related families ( Chang et al , 2016 ; Garg et al , 2016 ).…”
Section: Rapid Progress In Molecular Physiology and Genomics Applied mentioning
confidence: 99%
“…Most of the recent tomato cultivars are drought-sensitive at all stages of plant development; the stage of seed germination and early seedling growth are the most sensitive (Mishra, Rai, Kumar, Singh, & Pandey, 2016). Genetic variability among the modern cultivated tomato is limited owing to natural and artificial selection during domestication and evolution (Steinhauser et al, 2011), which makes tomato wild relatives a good source of drought tolerance genes.…”
Section: Introductionmentioning
confidence: 99%